Multicenter Study of Antibiotic Resistance Profile of H. pylori and Distribution of CYP2C19 Gene Polymorphism in Rural Population of Chongqing, China - Ran Han; Hong Lu; Ming-Wan Jiang; Ke-Wen Tan; Zhong Peng; Jia-Li Hu; Dian-Chun Fang; Chun-Hui Lan; Xiao-Ling Wu (Gastroenterology Research and Practice)
This study was to investigate the antibiotic resistance profile of H. pylori and the distribution of CYP2C19 gene polymorphism in rural population of Chongqing, China. 214 and 111 strains of H. pylori were isolated from rural and urban patients, respectively. 99.53%, 20.09%, and 23.36% of the isolates in rural patients were found to be resistant to metronidazole, clarithromycin, and levofloxacin, while the resistant rate in urban patients was 82.88%, 19.82%, and 24.32%. The multiple antibiotic resistance percentage significantly increased from 28.26% (below 45 years) to 41.80% (above 45 years) in rural patients. Up to 44.39%, 45.79%, and 9.81% of rural patients from whom H. pylori was isolated were found to be extensive metabolizers, intermediate metabolizers, and poor metabolizers. No correlation was observed between antibiotic resistance profile of H. pylori and genetic polymorphism of CYP2C19 among rural population. There was a high prevalence of H. pylori strains resistant to metronidazole, clarithromycin, and levofloxacin in rural patients in Chongqing, China. The choice of therapy in this area should be based on local susceptibility patterns. Amoxicillin, gentamicin, and furazolidone are recommended as the first-line empiric regimen.